2000
DOI: 10.1089/acm.2000.6.415
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary Medicine by Adult Patients Participating in HIV/AIDS Clinical Trials

Abstract: Subjects used a variety of CAM therapies to cope with their diseases and rigors of treatment and clinical trials. Further research is needed to identify CAM therapies that may be used as adjunct treatments during clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
167
2
7

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(190 citation statements)
references
References 12 publications
13
167
2
7
Order By: Relevance
“…CAM may add to or seek to replace conventional care, and recent commentators have used the phrase "integrative medicine" to foster more open debate. In a sample of HIV/AIDS patients enrolled in a clinical trial at the National Institutes of Health (NIH), 91% had used at least one CAM therapy [3]. A number of reports of the use of CAM among oncology patients cite a prevalence of 1 in 3.…”
Section: Discussion Prevalence and Costs Of Usementioning
confidence: 99%
See 1 more Smart Citation
“…CAM may add to or seek to replace conventional care, and recent commentators have used the phrase "integrative medicine" to foster more open debate. In a sample of HIV/AIDS patients enrolled in a clinical trial at the National Institutes of Health (NIH), 91% had used at least one CAM therapy [3]. A number of reports of the use of CAM among oncology patients cite a prevalence of 1 in 3.…”
Section: Discussion Prevalence and Costs Of Usementioning
confidence: 99%
“…They intimate that CAM resembles that antiquated and unjust system. Of the myriad reasons cancer patients seek CAM, a sense of helplessness, incomplete trust in physician, a changed outlook since cancer diagnosis, and a deteriorating functional quality of life are among the most generally voiced [45,51]. Patients battling serious ailments valued CAM for its medicinal potential.…”
Section: Harnessing Hope: Motives For Cam Usementioning
confidence: 99%
“…More recent studies have reported an even higher prevalence of between 70 and 80% (Richardson et al, 2000;Bernstein and Grasso, 2001;Ashikaga et al, 2002). The nature of CAMs used, for example, vitamins and other supplements, herbal remedies, physical and psychological treatments, also varies greatly (Risberg et al, 1998;Richardson et al, 2000;Sparber et al, 2000;Bernstein and Grasso, 2001;Ashikaga et al, 2002).…”
mentioning
confidence: 99%
“…The reasons for CAM use have been widely investigated. Patients often wish to combine conventional and CAM approaches to improve their quality of life, to counter side effects, to achieve a sense of control and to match their life style with their world view (Austin, 1998;Sparber et al, 2000;Kessler et al, 2001).…”
mentioning
confidence: 99%
“…They, like their patients, believe that CAM modalities can decrease side effects, but do not expect CAM to boost immunity or improve quality of life [17]. Strengthening the immune system is a common reason cited by patients, but not physicians, for DS use [18,19], as is a desire to decrease medication complications or relieve other symptoms, such as anxiety or depression [8,18]. While desire for a cure is less often stated as a reason, prevention of recurrence is a common reason for breast cancer patients to use CAM [19].…”
mentioning
confidence: 99%